Molecular containers in complex chemical systems. (16th July 2014) - Zarra, Salvatore; Wood, Daniel M.; Roberts, Derrick A.; Nitschke, Jonathan R.
Abstract : This review discusses recent advances in the use of molecular containers in complex chemical systems, focusing on three aspects: host–guest behaviour, structural transformations and reactivity modulation. Abstract : Over the last decade molecular containers have been increasingly studied within the context of complex chemical systems. Herein we discuss selected examples from the literature concerning three aspects of this field: complex host–guest behaviour, adaptive transformations of molecular containers and reactivity modulation within them.